ANALYSIS OF THE ROLE OF THE AMONG SYSTEM IN HABITUATING SCOUT ACTIVITIES AT SDN 066 HALIMUN - Edwina Attahiya Soebagyo; Eliza Budi Agustin; Elsa Dwi Melia Wardoyo; Dana Martienda; Elgina Mulya Utami; Elma Kharisma Dyah Ayu Sesanti; Eggie Nugraha (Politeknik Penerbangan Surabaya, 2026)
This study examines the implementation of the Among System in Scout activities at SDN 066 Halimun and explains how it contributes to elementary students' character habituation. Using a qualitative case study design, the study involved educators or Scout leaders and students who were directly engaged in routine Scout activities. Data were collected through semi-structured interviews, activity observations, and documentation of Scout programs, schedules, and school records. The data were analyzed thematically by comparing evidence from different participant groups and data sources. The findings show that the Among System is implemented through three interrelated principles: Ing Ngarso Sung Tuladha, Ing Madya Mangun Karsa, and Tut Wuri Handayani. These principles strengthen character habituation by modelling discipline, motivating active participation, and providing guided autonomy for students. The study also identifies technical and non-technical constraints, including limited facilities, limited guidance time, variation in student enthusiasm, and the need for consistent leader capacity. The study contributes to character education scholarship by showing how the Among System can function as a practical mentoring framework in Scout-based extracurricular learning. Practical implications include the need to strengthen school-parent-community collaboration, integrate Scout values into daily school routines, and provide continuous training for Scout leaders.